La mujer que supo gobernar un país ingobernable para Bolívar. Francisca Zubiaga desde el feminismo sansimoniano en Peregrinaciones de una paria - Denegri, Francesca (Pontificia Universidad Católica del Perú, 2025)
This article examines Flora Tristan's portrait of a female leader who gained notoriety for her open exercise of political power in the early Peruvian Republic. It argues that the feminist discourses that emerged during the revolutions of 1789, 1830 and 1848 in France, in particular Saint-Simonian feminism, along with the patriotic gender debate in Peru, constitute the central threads of this complex, foundational travel narrative. When the literary subject comes into contact with historical Peruvian female characters foreign to French imaginaries, her place of enunciation is destabilized and her visionary force is enhanced and magnified. In the process of constructing Zubiaga as a public figure, Tristan discovers a narrative space in which she can negotiate her own identity in the face of intensely antagonistic gender mandates; this reckoning will enable her reinvention as the leader of a new emancipatory politics of class and gender.

Este trabajo examina el retrato que elaboró Flora Tristán de una mujer caudilla que a inicios de la República peruana alcanzó notoriedad por su ejercicio abierto de poder político. Sostiene que los discursos feministas que eclosionaron en las revoluciones de 1789, 1830 y 1848 en Francia, en particular el sansimonismo, y el debate de género patriótico en el Perú constituyen los hilos más visibles del complejo entramado narrativo de su libro de viajes. Al entrar el sujeto literario en contacto con un escenario peruano poblado de personajes femeninos históricos ajenos a los imaginarios franceses, su lugar de enunciación se desestabiliza y potencia su fuerza visionaria. En el proceso de construir a Zubiaga como figura pública, Tristán descubre un espacio narrativo de negociación identitaria frente a mandatos de género en relación de intenso antagonismo, lo que le permitirá su reinvención como líder de una nueva política emancipatoria de clase y género.
The Woman Who Knew How to Govern Bolivar’s Ungovernable Country. A Saint-Simonian Reading of Francisca Zubiaga in Peregrinations of a Pariah
Keywords: Testimonio; Saint-Simonian feminist press; Female Caudillismo; Peregrinations of a Pariah; Testimonio; Prensa feminista sansimoniana; Caudillismo femenino; Peregrinaciones de una paria; https://purl.org/pe-repo/ocde/ford#6.02.06